Numerasi: Analisis Kesalahan Translasi Representasi - Murniasih, Tatik Retno; Suwanti, Vivi; Suastika, I Ketut; Farida, Nur; Yuwono, Timbul; Hanik, Umi (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2024)
This research aims to describe students' representational translation errors in solving numeracy problems. A qualitative method was employed in this study. The research subjects consisted of 24 elementary school students from a school in Malang Regency. The instruments used included tests, observation sheets, recording equipment, and field notes. The research process involved recording students' answers, identifying students who completed their work correctly but could not explain their answers, and categorizing students who made errors based on the type of error. The findings indicate that students experience translation errors in language representations, symbols, pictures, and analogies. The study recommends that teachers implement targeted learning interventions to support students who continue to make such errors.